The Effect Of Clove Compress Towards Rheumatoid Arthritis Pain On The Elderly In Banjar Uma Anyar, Pejeng Kaja Village, Tampaksiring - I Putu Artha Wijaya; Alfiery Leda Kio; Sang Ayu Komang Gangga Dewi (Universitas STRADA Indonesia, 2021)
This study aimed at determine the effect of clove compress on rheumatoid arthritis pain in Banjar Uma Anyar, Desa Pejeng Kaja Tampaksiring. This study was quantitative research that used Quasi-Experimental Designs with the Non-Equivalent Control Group type. Samples in this study were taken using nonprobability sampling technique namely purposive sampling, with a sample size of 30 respondents. This research instrument used an observation sheet. The results of the Mann Whitney U test analysis on the post-test of rheumatoid arthritis pain showed a probability value (sig) <0.05 (0,000 <0.05) therefore it could be concluded that in outline there was a difference in rheumatoid arthritis pain after providing clove compression to the intervention group. Based on the results of this study, it is expected that patients with rheumatoid arthritis pain can apply clove compress if rheumatoid arthritis appears in the morning and interfere with the elderly’s activities